Factors influencing impacts on and recovery trends of organisations: evidence from the 2010/2011 Canterbury earthquakes. (December 2015) - Brown, Charlotte; Stevenson, Joanne; Giovinazzi, Sonia; Seville, Erica; Vargo, John
Abstract: In 2010 and 2011, the Canterbury region of New Zealand was struck by a series of earthquakes, the most serious of which was a magnitude M=6.3 earthquake on 22nd of February 2011 centred near the heart of Christchurch city. This earthquake led to the cordoning of the central business district due to safety concerns, with parts of the city remaining closed to the public for more than two years following the earthquakes. With large numbers of organisations needing to relocate and being faced with ongoing infrastructure disruption, and significant concerns for staff welfare, the February 2011 Canterbury earthquake provides a valuable case study for enhancing understanding of how businesses are affected by and recover from disasters. In this paper, using data from 541 organisations affected by the Canterbury earthquakes, some of the main findings from the international literature are reassessed. In particular, the paper addresses which types of impact were more disruptive for organisations than others; and whether or not organisational demographics, including age, size, sector and property ownership, are predictors of an organisation's level of impact and recovery following a significant disaster. The paper finds that human/organisational issues, in particular 'Customer Issues' impacts were most disruptive for organisations. Furthermore, this paper finds that, contrary to much current literature, organisational age and size do not strongly predict disaster impact and recovery success. Sector was found to be a predictor of both impact and recovery. Organisations that rented recovered slightly more effectively than those that owned their properties. Highlights: The most disruptive impact for organisations in Canterbury was Customer Issues. Organisation age and size were not predictors of impact or recovery. Sector was a predictor of both impact and recovery for organisations. Organisations that rented recovered slightly better than those that only owned premises. Recovery trends differed noticeably when initial impacts were taken into account.